Gamelan Truntung Art in the Study of Structural Functionalism - Indariyana, Raditya Wahyu; Wadiyo, Wadiyo; Utomo, Udi (Universitas Negeri Semarang, 2018)
Gamelan Truntung is one of traditional arts in Magelang. This art derives from a mixture of Truntung with a set of gamelan instruments. Truntung is a musical instrument to accompany or facilitate Soreng dance which is also a traditional art in Magelang. The problem of the research is to answer how the structural functionalism of Gamelan Truntung Art is. The research is conducted to know, to analyze, and to describe the structural functionalism of gamelan Truntung art. Meanwhile, the research method applied is a qualitative method using monodisciplinary approach. The techniques used to collect the data needed in writing this article are obervation, interview, and document study. Then, the validity of the data collected is checked by applying data triangulation technique. The type of triangulation data used is the triangulation data of the resources which uses data analysis technique comprising of three steps, namely data reduction, data presentation, anda data verification. Gamelan Truntung art is considered as a system which has some parts that influence and are functional to each otherKesenian Truntung. The man in charge of the art studi or sanggar has run his function well, but in fact, there is a latent function which gives disadvantages to Gamelan Truntung art. The other part experience disfunction which hinders the development of Gamelan Truntung art. Gamelan Truntung can be maintained by giving attentions to the following, namely the artist creativity which must be elevated by having no dependency on Mr. Riyadi as the man in charge, and some hindering idealism which must be able to be set aside for the development and the progress of the art studio and its art.